Strange Crusader Adolf – on the Margins of Considerations about the Northern Crusade from 1147 - Pychowski, Michał Witold (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
Helmold from Bosau, describing the events preceding the Second Crusade, recalls about an attempt to discredit its main propagator – Bernard of Clairvaux. It consisted in forcing the future saint to accomplish the miracle of healing a lame boy. The author of this attempt was Count Adolf from Holstein. Although the events mentioned are similar to those contained in the hagiogrphy of Saint Bernard, however, do not remain in conection with them due to the chronology of the origin of the discussed sources. The basic reason for Adolf’s actions was probably an alliance with the Duke of Obodrites – Niklot, who was supposed to be the main target of the 1147 wendish expedition. The cooperation between the two feudals also became apparent during the armed struggle itself, and this alliance continued after the war. The specific attitude and political actions suggest that Adolf was a person who did not fully share the worldview and moral values of his time.